The Effect Of Digital Marketing And Product Variety On Purchase Decisions At Juragan Mode Shopin Bengkulu City - Delta R Landa; Ida Anggriani; Kamelia Astuty (Journal of Multidisciplinary Research, 2026)
This study, entitled "The Effect of Digital Marketing and Product Variety on Purchase Decisions at Juragan Mode Shop in Bengkulu City," aims to determine the extent to which digital marketing and product variety affect consumers’ purchase decisions. The background to this research stems from technological developments that encourage businesses, particularly in the fashion industry, to adapt through digital marketing strategies. Juragan Mode Shop, as one of the fashion shop in Bengkulu City, also utilizes social media and digital platforms to attract customers. However, sales success depends not only on digital promotions but also on the product diversity offered. The research method used was a quantitative method with an associative approach. The population in this study was all consumers who had shopped at Juragan Mode Shop, with a sample size of 100 respondents selected through purposive sampling. Data were collected using a questionnaire with a Likert scale and analyzed using multiple linear regression analysis using SPSS version 23. Validity and reliability tests, t-tests, F-tests, and coefficient of determination (R²) were used to verify the hypotheses and the reliability of the research instrument. Based on the results of the multiple linear regression test, digital marketing has a positive and significant effect on purchase decisions, with a regression coefficient of 0.738, a calculated t-value of 6.178, and a significance value of 0.000 < 0.05. Product variety also has a positive and significant effect, with a regression coefficient of 0.523, a calculated t-value of 2.993, and a significance value of 0.003 < 0.05. Simultaneously, both variables significantly effect purchase decisions, with a calculated F-value of 101.089 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.676 indicates that 67.6% of the variation in purchase decisions is explained by digital marketing and product variety, while 32.4% is influenced by other factors such as price, service quality, and brand image. In conclusion, the implementation of an effective digital marketing strategy and the availability of diverse products have been proven to increase consumers’ purchase decisions at the Juragan Mode Shop in Bengkulu City.